Practice and perceptions of classroom management: A study at the tertiary level - Rahman, Md Munibur (Asian Journal of Contemporary Education, 2024)
The successful dissemination of learning inputs and its success largely depends on how aptly the classroom management issues are managed and addressed. This study investigated the existing scenario of classroom management practices and teachers’ perceptions, and the impacts of the practices on fifteen specific classroom management strategies employed at the tertiary level in Bangladesh. With a structured questionnaire following a five-point Likert scale, 113 teachers from 56 departments of 38 universities were surveyed to collect data for this research. The study found that the teachers, students, the university authorities, classroom rules and disciplines, the physical environment of the classrooms, etc. were closely intertwined and the class size had both positive and negative impacts on the specific classroom management issues. The practices and teachers’ perceptions also implied that the teachers were quite capable of managing the issues that were directly under their control like the use of nonverbal communication or body language, changing the teaching strategies according to the proficiency levels of the students, etc. However, the classroom management issues like class size, infrastructure, etc. which were directly under the control of the university authority were not up to the standard. The findings of this research are expected to benefit the tertiary level classroom management system in Bangladesh and other countries by pointing out the issues to the teachers, policymakers, and education administrators.